Factors affecting medical tourism: A case study of Azeri tourists in Iran - Kiarash Shafizadeh; Mohammad reza Sohrabi; Navid Hezari (Shahid Beheshti University of Medical Sciences, 2018)
Health tourism is one of the effective factors in the economic prosperity of the countries, the beautiful nature and hot springs of Ardebil province makes it a good destination for health tourism. The aim of this study was to investigate demographic and socioeconomic characteristics of health tourists of Ardebil. To investigate the viewpoint of health tourists coming to Ardebil province from Azerbaijan, a comprehensive Turkish language questionnaire was designed by the researcher and by visiting medical centers in Ardebil and pharmacies and restaurants the questionnaires were completed. Out of 200 distributed questionnaires, 193 were completed. The average age of the participants was 26.23 years and often had less than 1800 USD monthly income. (184, 95.4%) of people were not covered by the general insurance of Azerbaijan. The cost of treatment and the total travel cost per person for participants was less than 120 USD. About the hospital services, one-third of respondents rated them (well). More than 95% of the tourist were from the border provinces. The lack of public insurance coverage in Azerbaijan and the higher value of the Azerbaijani manat compared to Iranian rial attract health tourists to Ardebil, but the quality of services provided needs to be improved . Government planners need to focus more on health tourism issues, especially in Ardebil so as to improve the infrastructures and remove barriers, it is a step towards the prosperity of this lucrative industry.